Indices for water quality assessment in a river - Mustapha, Norhayati; Lohani, B.N.; I, Fude.; Watanabe, Yoshimasa; Lee Foundation, Singapore (Bangkok : Asian Institute of Technology, 1981)
The study, which proved to be an interesting academic exercise, was imitated with the objective of quantitatively assessing the water quality of a river (namely the Linggi in Malaysia), by means of indices, e.g . the Rand Corporation's Delphi-method derived WQI, the Factor Analysis WQI and the Stochastics WQI. Thus three main techniques of Index Development were researched: the Opinion Poll Survey, Computing Methods and Statistics. In the process of reporting water quality in the Linggi and other river systems, Index types (e.g . Horton's, Prati's, Opinion Poll, Factor Analysis) and formulae (Arithmetic, Geometric, Maximum Operator) were studied and compared, Water in the Linggi was found to be in the 'Polluted' class for most reaches, (Index 30 to 60), the more upstream reaches registering 60 to 80 or 'Slightly Polluted' to 'Acceptable'. 'Ideal' level of 80 and above was hardly ever achieved except in isolated cases at the uppermost reach; river pollution attributed mainly to organic parameters such as BOD, ammoniacal nitrogen, oil and grease and bacterial content. The watercourse proved to be more favorable for agricultural irrigation than fish and wildlife; and least suited for direct consumption (with required treatment for public water supply increasing in intensity down river). Conditions seemed to have improved from 1978 to 1980, although in 1980 alone a slight decline in water quality was observed, calling for a possible re-assessment of environmental enforcement programmes. Eventual incorporation of developed indices into Planning, supplementary to the Probabilistic assessment by the Stochastic Approach, suggests a useful application of Indices into the Water Quality Management scheme of a river, whereby priority areas can be established and pollution -abatement measures carried out. As a result, proposals are put forward to the water quality management scheme for Linggi River in particular and the Malaysian network as a whole.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1981
Keywords: Water quality management -- Mathematical models